Neighborhood Diversity and the Appreciation of Native- and Immigrant-Owned Homes - Deborah A. Cobb-Clark; Mathias G. Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper examines the effect of neighborhood diversity on the nativity gap in homevalue appreciation in Australia. Specifically, immigrant homeowners experienced a 41.7 percent increase in median home values between 2001 and 2006, while the median value of housing owned by the native-born increased by 59.4 percent over the same period. We use a semi-parametric decomposition approach to assess the relative importance of the various determinants of home values in producing this gap. We find that the differential returns to housing wealth are not related to changes in the nature of the houses or the neighborhoods in which immigrants and native-born homeowners live. Rather, the gap stems from the fact that over time there were differential changes across groups in the hedonic prices (i.e., returns) associated with the underlying determinants of home values.
Keywords: F22; D31; 330; International migration; home-ownership; decomposition analysis; Wohneigentum; Nachbarschaftsökonomie; Migranten; Immobilienpreis; Multikulturell; Australien